1977
DOI: 10.1079/bjn19770110
|View full text |Cite
|
Sign up to set email alerts
|

The effects on glucose metabolism of feeding a high-urea diet to sheep

Abstract: 1. Sheep were given either a basal diet of 107 g crude protein (nitrogen x 6,25)/kg or the same diet to which urea was added to increase the crude protein content to 221 g/kg. Isotope-dilution techniques with [U-14C]glucose and [2-3H]glucose were used to measure various criteria of glucose metabolism. The plasma concentrations of urea and potassium were determined. The sheep were then given the alternative diet and the experiment was repeated.2. Plasma K concentrations were decreased on feeding urea (P < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…All values serum glucose levels of all treatments lie within the normal range which were 52-56 mg/dl in sheep 2.5-4 years (Eshratkhan et al, 2008;Mustafa et al,2009). Our results agreed with Leonard et al (1977) data who reported that serum glucose concentrations were 3.7 and 4.1 mmol/L of sheep fed urea diet and those fed free urea one respectively. As well as, Knaus et al (2002) observed that blood serum glucose level significantly decreased in steers fed diets containing urea in compared to those fed on untreated one.…”
Section: Effect Of Dietary Urea Level On Serum Glucose Concentrationsupporting
confidence: 93%
“…All values serum glucose levels of all treatments lie within the normal range which were 52-56 mg/dl in sheep 2.5-4 years (Eshratkhan et al, 2008;Mustafa et al,2009). Our results agreed with Leonard et al (1977) data who reported that serum glucose concentrations were 3.7 and 4.1 mmol/L of sheep fed urea diet and those fed free urea one respectively. As well as, Knaus et al (2002) observed that blood serum glucose level significantly decreased in steers fed diets containing urea in compared to those fed on untreated one.…”
Section: Effect Of Dietary Urea Level On Serum Glucose Concentrationsupporting
confidence: 93%
“…Increased blood glucose levels derive mainly from a reduced rate of tissue utilization of glucose but there is also an attendant reduction in the production of glucose via gluconeogenesis (Emmanuel & Edjtehadi, 1981). The fact that both production rate and utilization rate of glucose can be affected, presumably by separate mechanisms, probably explains the variation in reported effects of urea feeding on blood glucose concentrations (Leonard et al 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, the irreversible glucose loss rate is the rate at which glucose leaves the sampled compartment never to return to that compartment, while the glucose entry rate is the rate of entry of glucose into the sampled compartment [56]. A combination of data from publications which compared different types of tracers [27,28,43] showed that on average glucose entry rates are 40% higher than the irreversible glucose loss rates.…”
Section: Methodological Aspectsmentioning
confidence: 99%